Mexican Psittacids held in captivity in Puerto Escondido, Oaxaca and their welfare conditions: Mexican Psitacids held in captivity in Puerto Escondido - Buenrostro-Silva, Alejandra; García-Grajales, Jesús; García-Grajales, Jesús (Ecosistemas y Recursos Agropecuarios, 2021)
Many bird species such as parrots and parakeets are held in captivity in various cities in Mexico as ornaments and pets. This study aimed to record the number of Psittacid species kept in captivity in the city of Puerto Escondido, Oaxaca, along with assessing their welfare conditions. Information was obtained from 195 bird keepers from March to May 2014, using the “snowball” interview technique. Information about their birds’ cost of acquisition, the season of sale, feeding and care were recorded. Additionally, an assessment of the welfare status of each bird was performed. A total of 245 Psittacid individuals were recorded, and all were illegal. Eupsittula canicularis was the most common species, and Amazona autumnalis was the least common. The most frequent welfare condition found was the absence of feathers (73.5%), probably associated with excess stress caused by overcrowding. Keeping wild birds in captivity continues clandestinely; therefore, is necessary to create a local strategy that helps prevent the domestic use of the Psittacids as pets.